Isotope Mass Spectrometry as a Tool for Identifying Organic Tomatoes (Solanum lycopersicum L.) - Lev A. Oganesyants; Alexander L. Panasyuk; Elena I. Kuzmina; Dmitry A. Sviridov; Mikhail Yu. Ganin; Alexei A. Sсhilkin (Техника и технология пищевых производств)
Tomatoes (Solanum lycopersicum L.) are one of the most popular vegetables in the world. These days, Russian consumers prefer tomatoes labeled as organic. However, the agricultural industry often lacks instrumental methods to confirm the organic status of tomatoes. Isotope mass spectrometry is a promising method that can detect tomatoes that fail to meet organic standards. Isotopic values of total nitrogen and total carbon can be used to identify tomatoes as those grown on the field or as those cultivated in greenhouses enriched with carbon dioxide. The research featured 16 samples of tomatoes, 14 of which were purchased in Russian retail chains. Two samples were grown on the field without chemical fertilizers. The composition of stable carbon and nitrogen isotopes in the samples was determined using an IRMS Delta V Advantage isotope mass spectrometer with additional auxiliary modules. In the greenhouse tomatoes, δ13C values ranged from –44 to –32‰. In the samples obtained from a conventional greenhouse, δ13C values ranged from –30 to –24‰. Six samples proved to have been grown in artificial carbon dioxide atmosphere. Three samples demonstrated borderline values of δ13C and δ15N; they were impossible to identify as organic or conventional, both in terms of artificial carbon dioxide and fertilizers. Isotope mass spectrometry proved to be efficient in detecting falsified organic products. Tomatoes grown with carbon dioxide enrichment had lower isotope values of total carbon than organic tomatoes. The obtained values also made it possible to tell between organic and chemical fertilizers.